Perancangan Interior Music Center di Surabaya - Diana Thamrin, Ricky Daniel Febriawan Adi Santosa (Intra, 2016)
The advanced development of music makes the musician do the same thing. The music store nowadays already answered every needs, but thereâs no music store which become the center where every music instrument are provide there. This music center is a design that has never existed before in Indonesia, where the design includes a complete music equipment sales according to each classification, and also a facility for musician and non-musician to gather and learn together about music. By combining those two aspects, which has the benefit of each aspect, aims to spurring interest in music as well as expand relations and to support productivity in the world of music society, especially at Surabaya